2021
DOI: 10.1186/s40337-021-00484-8
|View full text |Cite
|
Sign up to set email alerts
|

Binge eating among older women: prevalence rates and health correlates across three independent samples

Abstract: Background Emerging research indicates that binge eating (BE; consuming unusually large amounts of food in one siting while feeling a loss of control) is prevalent among older women. Yet, health correlates of BE in older adult populations are poorly understood. The original study aimed to investigate BE prevalence, frequency, and health correlates in a sample of older adult women. Based on results from this first study, we then sought to replicate findings in two additional samples of older adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…In the current sample with a mean age of almost 69 years, 18% reported engaging in BE weekly or more frequently over the past few months. This is consistent with recent research, which found rates of weekly BE ranging from 19 to 26% across three independent samples of older adult women [55]. Another study found that 12% of older women reported BE in the past month, while 19% reported episodes of loss-of-control eating [7].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current sample with a mean age of almost 69 years, 18% reported engaging in BE weekly or more frequently over the past few months. This is consistent with recent research, which found rates of weekly BE ranging from 19 to 26% across three independent samples of older adult women [55]. Another study found that 12% of older women reported BE in the past month, while 19% reported episodes of loss-of-control eating [7].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, we did not use targeted recruitment for women with eating concerns, which could have artificially inflated the rates of BE as well as the relations between BE and health indices. Indeed, the consistency in observed rate of weekly BE in our sample with past research [7,55] is a strength of this study. Measures demonstrated strong psychometric properties in our sample, supporting participants attended to measures during online assessment, and this was verified through data quality checks.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Past researchalso suggests thatearlypostmenopausal womenwere two to four times more likely to experience a major depressive episode than premenopausal women, 16 while 41% of post-menopausal women reported mild depression in a separate study 17 . Finally, binge eating (ie, consuming abnormally large amounts of food in one sitting while simultaneously feeling out of control) is the most common form of disordered eating among older adult women (eg, 12%-20%) 18,19 . Overall, research demonstrates the role that the menopausal transition plays in the mental health and QOL of women, which can persist across all stages of menopause.…”
mentioning
confidence: 99%
“…17 Finally, binge eating (ie, consuming abnormally large amounts of food in one sitting while simultaneously feeling out of control) is the most common form of disordered eating among older adult women (eg, 12%-20%). 18,19 Overall, research demonstrates the role that the menopausal transition plays in the mental health and QOL of women, which can persist across all stages of menopause.…”
mentioning
confidence: 99%